Design and fabrication of foldable and adjustable desk / Muhammad Ammar Amsyar Azran - Azran, Muhammad Ammar Amsyar (2022)
In Malaysia, offices and education institutes are the backbone that contributes in increasing the economy and achievement of this country. However, the workers and students have give less and less priority in inventing a model that would make their work easier. As an example, during this pandemic mostly they work and study from home. So, they need the desks with portable and height adjustable properties because it will burden some of the desk consumers to buy many desks with different height. It also requires a lot of space to use all of the desks. In this adjustable desk project, some innovation will make which different from current desk in the market. Adjustable Desk instantly turns a desk or table into an moving desk for reading, writing and work centre. The desk must have foldable and adjustable so it can use for all ages and people with different height in daily life routine. Skill requirement during making this project is Solidwork, mechanical design and basic machining such as drilling and bonding